Efectos de la incorporación de diferentes niveles de harina de cascara de maracuyá (Passiflora edulis) sobre los parámetros zootécnicos en cuyes (Cavia porcellus), en la etapa de recría – acabado - BALDEON ESTRADA, MARCOS ANTHONY (2023)
The research was carried out on the premises of the Faculty of Science, located at km 7.5 of the road Babahoyo - Montalvo, Province of Los Rios, whose geographical location with UTM coordinates were X: 669 097.17; Y: 9'801 368.24, is at an altitude of 8 meters above sea level (masl). The area has a humid tropical climate, with an average temperature of 24 and 26 ° C, with a relative humidity of 88%, a duration of 30 days. The objectives were: To analyze the effect of passion fruit (Passiflora edulis) husk meal as a feed supplement on the zootechnical parameters (live weight gain, final weight, feed conversion and carcass yield) of guinea pigs. Determine the best treatment based on the level of passion fruit (Passiflora edulis) peel incorporated in the diet as a feed supplement. To evaluate the production costs of the treatments under study. Sexual condition (male-female) did not affect the productive response of guinea pigs (P˃0.05). The levels of passion fruit meal inclusion influenced (P>0.05) final weight, weight gain and carcass yield.